1999
DOI: 10.1177/074171369905000103
|View full text |Cite
|
Sign up to set email alerts
|

A Model of College Outcomes for Adults

Abstract: This article presents a model of college outcomes for adult undergraduate students to address the key elements that affect their learning and to stimulate research and theory building about adults' experience in college. It provides a review of the literature and a comprehensive model that considers the relationships between six major elements related to adults' undergraduate collegiate experiences: (a) prior experiences; (b) orienting frameworks such as motivation, self-confidence, and value system; (c) adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
101
1
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 41 publications
5
101
1
4
Order By: Relevance
“…Although we did not find differences across age groups, our findings do support the research within the adult education literature on the primacy of the classroom as a source of collegiate engagement. Donaldson and Graham (1999) note that in their model of college outcomes for adults, "the classroom is seen as the fulcrum of the collegiate experience . .…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find differences across age groups, our findings do support the research within the adult education literature on the primacy of the classroom as a source of collegiate engagement. Donaldson and Graham (1999) note that in their model of college outcomes for adults, "the classroom is seen as the fulcrum of the collegiate experience . .…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers have focused on persistence in traditional students, excluding the experiences of adult learners (Donaldson & Graham, 1999). Widely accepted models of student persistence describe the concept in terms of student retention and outcomes (Donaldson & Graham, 1999). Bean (1 990) and Tinto (1 993) argued that persistence is strongly related to a student's commitment to a college or university.…”
Section: Adult Learner Persistencementioning
confidence: 99%
“…Authors have recently identified ways in which adult learner persistence may differ from traditional definitions and have noted a lack of research that guides our understanding of persistence patterns in this significant student population (Donaldson & Graham, 1999;Naretto, 1995). One issue emphasized in the literature relates to adult learners' academic expectations and demands on their time and energy.…”
Section: Adult Learner Persistencementioning
confidence: 99%
See 2 more Smart Citations